Strategi Manajemen Psikologi Dalam Meningkatkan Kesejahteraan Karyawan - Thoyyibah, Wardatut; Hajar, Devi Dewi; Sari , Kurnia; Fitriyah , Nayyifatul; Mualimin, Mualimin (YPI Ulul Albab, 2025)
Employee well-being depends not only on material factors but also on psychological conditions and the social environment at work. This study explores psychological management strategies using a socio-emotional approach, emphasizing healthy interpersonal relationships, openness, and appreciation of diversity. Organizational leaders act as facilitators in creating a supportive work climate. The results show that effective communication and emotional support can enhance employees’ motivation, sense of belonging, and psychological well-being.